Legal Analysis of the Implementation of Agreements For Palm Oil Products Between PT. Peaceful Jaya Lestari with Land Ownership in Kolaka District - -, Tamal; Pattenreng, H.A.Muh. Arfah; Makkawaru, Zulkifli (Postgraduate Bosowa University Publishing, 2018)
This study aims to determine the form of cooperation agreement between PT. Damai Jaya Lestari with community land owners in Tanggetada Subdistrict and factors that influence the implementation of the production sharing agreement. This research was carried out at PT. Damai Jaya Lestari and the land-owning community in Tanggetada District, Kolaka Regency. The method used is to use a quantitative approach with the aim to analyze the form of profit sharing agreement between PT. Damai Jaya Lestari with the landowner community in Tanggetada Subdistrict as well as factors that influence the implementation of the production sharing agreement. The results of this study indicate that the form of production sharing agreement between PT. Damai Jaya Lestari with the landowner community is a written form with a profit sharing of 40:60, which is 40% for the landowner community and 60% for the company. For people who are 40% are subject to deductions for maintenance and exploitation costs, so that what is accepted by the land owners is little. However, there is no deduction of 60% for companies. The factors that influence the implementation of the production sharing agreement are the lack of education and the knowledge of the landowners, the details of the agreement are not explained in detail by the company, and there are irresponsible individuals.